RACIAL CONSIDERATIONS ARE A PREREQUISITE AND NOT AN AFTERTHOUGHT: A DISCUSSION OF Kroukamp v The Minister of Justice and Constitutional Development [2021] ZAGPPHC 526 and Magistrates Commission v Lawrence 2022 1 All SA 321 (SCA) - Mabaso, Fanele (Obiter, 2023)
This case note engages in a critical examination of two recent cases concerning the issue of race-based appointments, or rather the lack thereof, in the judiciary. The crux of this case note concerns the appointment of judicial officers as regulated by section 174 of the Constitution of the Republic of South Africa, 1996 (Constitution). In particular, the case note is driven by subsection 2 of section 174, which provides:“The need for the judiciary to reflect broadly the racial and gender composition of South Africa must be considered when judicial officers are appointed.”In essence, this case note is an advocate for the argument that the South African judiciary must reflect the demographics of the country. That is to say, racial considerations are a prerequisite in judicial appointments, and not an afterthought. The case note starts with a discussion of the matter that was before the Gauteng High Court, sitting as the Equality Court, in Kroukamp v The Minister of Justice and Constitutional Development ([2021] ZAGPPHC 526). The case note then discusses the later decision of the Supreme Court of Appeal in Magistrates Commission v Lawrence (2022 1 All SA 321 (SCA)).